KARAKTERISASI NUGGET PINDANG IKAN-AMPAS TAHU YANG DITAMBAH TEPUNG TULANG IKAN SEBAGAI SUMBER KALSIUM - Hardoko Hardoko; Eddy Suprayitno; Titik Dwi Sulistiyati; Alfin Adam Arifin (Universitas Pelita Harapan, 2017)
ABSTRACT. The bones of the boiled fish contain high calcium that can be used for osteoporosis therapy, but less utilized in food products. This study was aimed to study the characteristics of boiled fish nugget mixed with okara as filler and added fish bone flour as a source of calcium. The method used was experimental method which was divided into 2 stages, namely the addition of okara 20, 30, 40% and the addition of fish bone flour of 60, 80, 100 mesh with concentration of 10, 20 ,30%. The results showed that the addition of okara could increase the water content of the nuggets, but has not yet affected the texture of the boiled fish nugget. In general, boiled fish nugget which had the highest panelists’ acceptance was the one that was added with 30% okara. The addition of fish bone flour tends to decrease water content and increases the texture of hardness boiled fish nugget -okara. The addition of fish bone flour to boiled fish nugget that had the highest panelists’ acceptance was fish bone flour of 10% with size of 100 mesh. The boiled fish nugget -okara contains 5.8 mg/g of calcium and 5.11% dietary fiber.Keyword : boiled fish nuggets, fish bone flour, okara